Saving the ghost of the mountain : an expedition among snow leopards in Mongolia - Montgomery, Sy (Houghton Mifflin Books for Children, 2009)
Provides an account of an expedition mounted by the Snow Leopard Trust to the mountains of Mongolia in an effort to learn more about the elusive snow leopard and find ways to keep it from extinction.